Comparing relationships between health-related behaviour clustering and episodic memory trajectories in the United States of America and England: a longitudinal study - Jing Liao; Shaun Scholes; Claire Mawditt; Shannon T. Mejía; Wentian Lu (BMC, 2022)
Abstract Background Health-related behaviours (HRBs) cluster within individuals. Evidence for the association between HRB clustering and cognitive functioning is limited. We aimed to examine and compare the associations between three HRB clusters: "multi-HRB cluster", "inactive cluster" and "(ex-)smoking cluster" (identified in previous work based on HRBs including smoking, alcohol consumption, physical activity and social activity) and episodic memory trajectories among men and women, separately, in the United States of America (USA) and England. Methods Data were from the waves 10-14 (2010-2018) of the Health and Retirement Study in the USA and the waves 5-9 (2010-2018) of the English Longitudinal Study of Ageing in England. We included 17,750 US and 8,491 English participants aged 50 years and over. The gender-specific HRB clustering was identified at the baseline wave in 2010, including the multi-HRB (multiple positive behaviours), inactive and ex-smoking clusters in both US and English women, the multi-HRB, inactive and smoking clusters in US men, and only the multi-HRB and inactive clusters in English men. Episodic memory was measured by a sum score of immediate and delayed word recall tests across waves. For within country associations, a quadratic growth curve model (age-cohort model, allowing for random intercepts and slopes) was applied to assess the gender-stratified associations between HRB clustering and episodic memory trajectories, considering a range of confounding factors. For between country comparisons, we combined country-specific data into one pooled dataset and generated a country variable (0 = USA and 1 = England), which allowed us to quantify between-country inequalities in the trajectories of episodic memory over age across the HRB clusters. This hypothesis was formally tested by examining a quadratic growth curve model with the inclusion of a three-way interaction term (age × HRB clustering × country). Results We found that within countries, US and English participants within the multi-HRB cluster had higher scores of episodic memory than their counterparts within the inactive and (ex-)smoking clusters. Between countries, among both men and women within each HRB cluster, faster declines in episodic memory were observed in England than in the USA (e.g., b England versus the USA for men: multi-HRB cluster = -0.05, 95%CI: -0.06, -0.03, b England versus the USA for women: ex-smoking cluster = -0.06, 95%CI: -0.07, -0.04). Additionally, the range of mean memory scores was larger in England than in the USA when comparing means between two cluster groups, including the range of means between inactive and multi-HRB cluster for men (b England versus the USA = -0.56, 95%CI: -0.85, -0.27), and between ex-smoking and multi-HRB cluster for women (b England versus the USA = -1.73, 95%CI: -1.97, -1.49). Conclusions HRB clustering was associated with trajectories of episodic memory in both the USA and England. The effect of HRB clustering on episodic memory seemed larger in England than in the USA. Our study highlighted the importance of being aware of the interconnections between health behaviours for a better understanding of how these behaviours affect cognitive health. Governments, particularly in England, could pay more attention to the adverse effects of health behaviours on cognitive health in the ageing population.